Single center experience in localization of insulinoma by selective intraarterial calcium stimulation angiography - a case series of 15 years - Halmi, Sándor; Berta, Eszter; Diószegi, Ágnes; Sira, Lívia; Fülöp, Péter; Nagy, Endre V.; Győry, Ferenc; Kanyári, Zsolt; Tóth, Judit; Bhattoa, Harjit Pal; Bodor, Miklós (Frontiers in Endocrinology, 2024)
Background Insulinomas are rare insulin-secreting neuroendocrine neoplasms of the pancreas. First-line treatment is the surgical removal of the tumor, however, the localization with standard imaging techniques is often challenging. With the help of selective intraarterial calcium stimulation the insulinoma’s localization can be narrowed down to one third of the pancreas which the selected artery supplies. Objective We aimed to prove the usefulness of the calcium stimulation test in case of 9 patients treated between 2006 and 2021 diagnosed with endogenous hyperinsulinemic hypoglycemia confirmed by fasting test, where conventional imaging methods, like transabdominal ultrasound, CT or MRI failed to detect the source of hyperinsulinemia. Methods We performed selective intraarterial calcium stimulation with angiography with calcium gluconate injected to the main supporting arteries of the pancreas (splenic, superior mesenteric and gastroduodenal arteries); blood samples were obtained from the right hepatic vein before, and 30, 60 and 120 seconds after calcium administration. Results With selective angiography we found a significant elevation of insulin levels taken from the right hepatic vein in five of the nine cases. On histopathology, the lesions were between 1-2 cm, in one case malignancy was also confirmed. In four patients we found a significant rise of insulin levels obtained from all catheterized sites, which confirmed the diagnosis of nesidioblastosis. In three cases no surgery was performed, and the symptoms relieved with medical treatment. Conclusions Selective intraarterial calcium stimulation remains an important tool in localization of the source of insulin excess, especially in cases where other diagnostic modalities fail.